Ependymoblastoma with pulmonary metastasis in an adolescent: A case report - Xu, Xinmin; Li, Angcheng; Xu, Xia; Gong, Qiangjun; Zhu, Shengjie; Chu, Wenya; Ding, Shubo (Frontiers in Neurology, 2022)
Ependymoblastoma is a rare embryonal neoplasm of the nervous system, and the entity is even rare with distant metastasis. This case can help refine the existing literature and provide lessons for the management of other patients with ependymoblastoma. The present case concerns an adolescent with supratentorial ependymoblastoma, who received gross-total resection (GTR), postoperative radiotherapy, and six cycles of chemotherapy, with disease-free survival (DFS) of about 5.3 years. Subsequently, pulmonary metastasis occurred, but no intracranial lesion was found. Finally, combined treatment with radiotherapy and chemotherapy significantly reduced the lung lesions, with progression-free survival (PFS) of 10 months and long-term survival of 6.3 years. This case indicates that the lung metastases of ependymoblastoma are relatively sensitive to radiation, but lung metastases have not completely disappeared. Perhaps, increasing the radiation dose to lung metastases can improve the efficacy, which is worth exploring.